An Estimation of the Safety Risk Factors Encountered During Tower Crane Installation and Dismantling on Construction Sites in Vietnam - Ngo , Thanh Long (International Journal of Sustainable Construction Engineering and Technology, 2023)
The construction field has an important and meaningful role in the economy of any nation, especially developing nations. However, construction is one of the most dangerous fields and has the highest rate of accidents, including deaths and disabling injuries in the world. The construction field uses many tower cranes, especiallyfor constructing multi-storey buildings, factories, or in urban areas, and requires an increasing number of tower cranes. Tower cranes certainly contribute to the high rate of construction injuries and fatalities, in which tower crane installation and dismantling take a high rate. Accidents during tower crane installation and dismantling can kill people (workers and citizens) as well as delays in construction schedules of project and/or damage to buildings and machines under construction. As a result, the cost of costruction projects can increase. In this paper, safety risk factors during tower crane installation and dismantling on construction sites in Vietnam are estimated by showing their likelihood of occurrence, degree of influence, and risk levels. A suitable-structured questionnaire was produced and sent to get data that had their likelihood of occurrence and degree of influence by applying a five-point Likert scale. The results showed that “Time constraints are requested by investor, principal contractor or employer” is the most likely factor with a mean value of 3.60 and “Break of a wire rope occurring on dismantling” has the highest degree of influence, with a mean value of 4.18. The result also showed that there are 15/21 factors with a moderate risk level that is acceptable but, requires suitable controls to maintain a safe working condition of tower crane installation and dismantling. The results of the paper may help managers as well as practicians with good understandings of how to advance the safety of tower crane installation and dismantling on construction sites in Vietnam.